Assessing Institutional Measures to Protect Women with Special Needs in Cameroon - Tangwa Modestine Ginje, Ph.D (European Science Publishing, 2023)
Women with special needs in most societies including Cameroon have been termed the most vulnerable as a result of their sex and disability. Not only are this women the weaker sex but are also plagued by disability which makes them more vulnerable to attack, violence, marginalization, discrimination and social exclusion. In order to protect this group, the UN mandates state parties to the 2006 Convention on the Rights of Persons with Disabilities to take positive measures to afford adequate protection for this very vulnerable group of women. Despite respecting the call of the UN, the institutional measures put in place to protect this woman in Cameroon are found lacking given that they still live in lack and total disregard of the fundamental human rights.
Keywords: Women with Special Needs, Vulnerable, Disability, Protection, Rights.